Bimetallic Au-Ag Nanoparticles Loaded Nanofibers for the Potential Treatment Against Antimicrobial Resistant Wound Infections : - Malik Kumar, Ankit (IIT(BHU) Varanasi, 2026)
Abstract is available in the attachment.
Keywords: Pharmaceutical Engineering and Technology